Tubulinosema pampeana sp. n. (Microsporidia, Tubulinosematidae), a pathogen of the South American bumble bee Bombus atratus - Plischuk, Santiago (2015)
An undescribed microsporidium was detected and isolated from the South American bumble bee Bombus atratus collected in the Pampas region of Argentina. Infection intensity in workers averaged 8.2 107 spores/bee. The main site of infection was adipose tissue where hypertrophy of adipocytes resulted in cyst-like body formation. Mature spores were ovoid and monomorphic. They measured 4.00 lm 2.37 lm (fresh) or 3.98 lm 1.88 lm (fixed). All stages were diplokariotic and developed in direct contact with host cytoplasm. Isofilar polar filament was arranged in 16 coils in one or, posteriorly, two layers. Coiling angle was variable, between perpendicular and almost parallel to major spore axis. Late meronts and sporogonial stages were surrounded by vesicles of approximately 60 nm in diameter. Based on both new and already designed primers, a 1827 bp (SSUrRNA, ITS, LSUrRNA) sequence was obtained. Data analyses suggest that this microsporidium is a new species of the genus Tubulinosema. The name Tubulinosema pampeana sp. n. is proposed.